The impact of cold deformation, annealing temperatures and chemical assays on the mechanical properties of platinum - Trumić B.; Stanković D.; Ivanović A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to form the necessary data base on platinum and platinum metals, certain tests were carried out on platinum samples of different purity of 99.5%, 99.9% and 99.99%. The degree of cold deformation, annealing temperature and chemical assays were tested as well as their impact on the mechanical properties of platinum. The Vickers hardness (HV) values were determined with different deformation degree, starting from annealing temperatures for platinum of different purity and tensile strength (Rm), flow limit (Rp0,2) and elongation (A) in the function of annealing temperatures and annealing time at a constant deformation degree.